2019
DOI: 10.1002/hrdq.21375
|View full text |Cite
|
Sign up to set email alerts
|

The development of emotional intelligence, self‐efficacy, and locus of control in Master of Business Administration students

Abstract: Successful managers must develop strong interpersonal skills alongside their ability to achieve personal and organizational goals. For educational institutions to stay relevant, courses must equip students with necessary psychological competencies in addition to technical knowledge, skills and abilities for the constantly evolving business climate. We explored whether Master of Business Administration (MBA) programs aid in the development of psychological competencies, given that MBAs are a popular management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 73 publications
1
30
1
Order By: Relevance
“…EI stops adopting uncivil behavior and fosters trust and enhances commitment (Giao et al, 2020;Thompson et al, 2020). Beauvais et al (2017) argued EI allows treating others the way people want to be treated themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EI stops adopting uncivil behavior and fosters trust and enhances commitment (Giao et al, 2020;Thompson et al, 2020). Beauvais et al (2017) argued EI allows treating others the way people want to be treated themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers viewed emotional self-efficacy as having the confidence that the activities at the workplace can be controlled by an individual working at any level. This is more effective when employees develop emotional self-efficacy and have a positive impact on the overall organizational environment (Thompson et al, 2020). Kelly and Kaminskienė (2016) argued that EI reduces the disputes and the people having emotional controls wisely resolve the conflicts via negotiation and mediation processes.…”
Section: Emotional Intelligence (Ei) As a Mediatormentioning
confidence: 99%
“…The relationship between self-efficacy and locus of control is widely investigated [ 14 , 15 , 16 ], confirming that they both are interrelated and affect the ability of the person to adjust in a given situation. Some research [ 17 , 18 , 19 , 20 ] has shown a positive relationship between self-efficacy and internal locus of control, describing how people who believe they have control over future events are more likely to use that control to achieve a positive result and experience enhanced wellbeing [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most relevant scientific contributions analyze the effects of leadership on the improvement of interpersonal skills and the ability to reach personal and organizational objectives. In higher education studies, the research includes how to provide students with the necessary psychological competencies, skills, and abilities required to deal with a constantly evolving business climate (Thompson et al, 2019). Thus, a growing number of studies are focusing on the competencies required to generate an impact on business organizations, such as self-efficacy, leadership, and locus of control.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a growing number of studies are focusing on the competencies required to generate an impact on business organizations, such as self-efficacy, leadership, and locus of control. In fact, leadership plays a key role in these studies in terms of the actions developed through leadership, their reception among organizational groups, and the impact generated on business organizations (Mumford et al, 2007;Thompson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%